Identifkasi Bahaya, Penilaian, dan Pengendalian Risiko Proses Pengangkutan Batu Bara di PT Alam Karya Gemilang Kabupaten Kutai Kartanegara Provinsi Kalimantan Timur - Fathurrahman Sufi; Lina Yuliana; Yan Fuadi (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
Transportation of coal production results is an activity of moving coal from the front loading area to the storage area for further transportation to the barge. The process of transporting coal is an important activity in mining activities that have a very high occupational health and safety risk. The purpose of conducting this research is to improve hazard, risk assessment, and control in the coal hauling process carried out by PT Alam Karya Gemilang. The type of research method used is descriptive qualitative research. This research method is used to describe descriptively the assessment and control of occupational safety and health risks using the hazard identification risk assessment risk control (HIRARC) method at PT Alam Karya Gemilang. Data collection was carried out by direct field observation and interviews with unit operators, field supervisors, and safety personnel in the field. The results of the study contained 16 hazards which included: slippery front area, narrow front area, loading coal during the day and night, dusty roads, foggy roads, damaged units, blind spot areas, exhaust emissions, interaction with heavy equipment units, slippery roads, and bumpy roads. And of the 21 hazards there are 24 identified risks, namely 4 hazards with low risk, 8 hazards with moderate risk, and 13 hazards with high risk. Controls carried out are administrative controls and engineering techniques.